Photoprotection and abnormal cutaneous photosensitivity. (October 2011) - Calzavara-Pinton, PierGiacomo; Rossi, MariaTeresa; Sala, Raffaella; Venturini, Marina
Sun exposure induces a broad range of skin reactions, the so-called photodermatoses. This group includes immunologically mediated photosensitive disorders, drug- or chemical-induced photosensitivity reactions, genetic diseases and photoexacerbated dermatoses. The clinical diagnosis may be difficult if skin lesions heal spontaneously before medical examination, and a careful phototesting is needed. The management of the 'photosensitive'' patient includes photoprotection (e.g., sun avoidance and the use of sunscreens), preventive phototherapy and medical treatment of acute flares. The suitable sunscreen should match the individual action spectrum of the disease and it should have a filtering activity proportional to the light threshold. Unfortunately, only few studies with a good experimental design are available so far. Oral and topical antioxidants are often used as well, but further studies are needed to assess their efficacy.